2024
DOI: 10.1002/adfm.202310181
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure Engineering in NiFe Sulfide via A Third Metal Doping as Efficient Bifunctional OER/ORR Electrocatalyst for Rechargeable Zinc‐Air Battery

Fitri Nur Indah Sari,
Yi‐Cheng Lai,
Yan‐Jia Huang
et al.

Abstract: Ti, V, Cr, Mn, Co, and Cu, have been investigated as a third dopant in NiFe sulfide for enhanced oxygen evolution reaction (OER)/oxygen reduction reaction (ORR). The effects of dopant on surface electronic structure, conductivity, and thermodynamic barrier of reaction are addressed and discussed. For the OER, X‐ray photoelectron spectroscopy analysis shows that electron transferring from the Ni to the dopants enhances the catalytic performance of the sulfide. Cu doped NiFe sulfide exhibits the best OER perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In light of growing global demand for energy and the heightened attention to environmental pollution issues, energy conversion and storage technologies, particularly fuel cells and metal-air batteries, have garnered significant interest due to their notable energy efficiency and environmental protection characteristics. However, the most formidable challenge associated with these technologies is the relatively slow kinetics of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), which occur alternately during the discharge and charge processes. Furthermore, the multistep four-electron transfer in the electrochemical process of zinc–air batteries (ZABs) has typically been constrained by a large potential gap (>0.85 V) and low energy efficiency. Currently, the majority of commercial ORR and OER catalysts are based on noble metal materials, such as Pt and RuO 2 . However, the scarcity, high cost, and stability issues of precious metals limit their large-scale application.…”
Section: Introductionmentioning
confidence: 99%
“…In light of growing global demand for energy and the heightened attention to environmental pollution issues, energy conversion and storage technologies, particularly fuel cells and metal-air batteries, have garnered significant interest due to their notable energy efficiency and environmental protection characteristics. However, the most formidable challenge associated with these technologies is the relatively slow kinetics of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), which occur alternately during the discharge and charge processes. Furthermore, the multistep four-electron transfer in the electrochemical process of zinc–air batteries (ZABs) has typically been constrained by a large potential gap (>0.85 V) and low energy efficiency. Currently, the majority of commercial ORR and OER catalysts are based on noble metal materials, such as Pt and RuO 2 . However, the scarcity, high cost, and stability issues of precious metals limit their large-scale application.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the ORR E 1/2 was increased from 0.77 to 0.84 V. The OER overpotential was reduced to 268 from 329 mV 17. Sari et al showed that V reduced the Ni 2+ /Ni 3+ ratio to optimize the electronic structure of the Ni active site and obtain a ZAB's superior cycle stability of 2400 cycles at a current density of 10 mA cm −2 18. Zhang et al proposed a model etching strategy to increase the Co 2+ /Co 3+ ratio of Co 3 O 4 19.…”
mentioning
confidence: 99%